Analysis of Rheological Phenomena in Reinforced Concrete Cross-section of Rędziński Bridge Pylon based on in Situ Measurements. (2015) - Bednarski, Łukasz; Sieńko, Rafał; Howiacki, Tomasz
Abstract: The creep of concrete is a phenomenon that is often the cause of excessive deformation of the structure in serviceability limit state. In fact, creep strains are generally larger than elastic strains which occur on the application of load. Creep is affected by many factors both internal - related to the properties of specific concrete and external - related to the operating environment. In addition, attention should be paid to the fact that in real structures concrete almost always interacts with the reinforcement. This article examines the rheological phenomena that occur in the reinforced concrete cross-section of the Rędziński Bridge pylon in Wrocław, using in situ measurements from an automated structural health monitoring system.